Experimental Studies on the Systemic Toxicity and Biodistribution of Synthesized Calcium Phosphate Nanoparticles After Oral Administration in Rats - C. Joshi, Jagdish; Bhardwaj, Anuradha; Roy, Indrajit; Gulati, Kavita; Ray, Arunabha (Pharmaceutical Nanotechnology, 2016)
Background and Objective: Nanoparticles have special properties, such as higher surface-to-volume ratio and higher reactivity, which increases cell penetrability and enhance their applicability in the field of medicine, especially in the case where other drugs are ineffective. Calcium phosphate nanoparticles (CPNP) and their encapsulation with therapeutic and/or diagnostic agents is such an agent synthesized. However, there are concerns related to the colloidal stability of these nanoparticles, which are reflected in their tendency to form aggregates in the physiological milieu. Therefore, successful translation of these nanoparticles from laboratory to the clinic requires studies of biodistribution and biocompatibility of nanoparticles for in vivo biomedical applications. Method: Calcium phosphate nanoparticles synthesized and were tagged with a fluorophore and surface stabilized with trisilanol for stable aqueous dispersion. The in vivo biodistribution and sub-acute toxicological studies were done for orally-administered calcium phosphate nanoparticles. Results: The biodistribution studies indicated that these nanoparticles were not prone to rapid degradation or excretion in the body, were long-circulating, and could appreciably permeate to the brain. Body/organ weight and biochemical analyses did not reveal much difference between nanoparticle-administered and saline-administered (control) groups. Finally, histopathological analyses of major organs such as liver, lungs, heart, stomach and kidney, did not reveal significant abnormalities in the treatment groups. Conclusion: Thus, it is evident from these sub-acute toxicity studies that the nanoparticles appear to be non-toxic to rats following oral administration. These observations can have significant implications in calcium-phosphate nanoparticle-mediated non-toxic drug delivery to target organs, such as brain, via non-invasive, oral route.
Keywords: sub-acute toxicity